Cryptocurrency sebagai Upaya Korea Utara untuk Mendapatkan Hard Currency - Junior Sembiring (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes why North Korea utilizes cryptocurrency as an effort to obtain hard currency. North Korea’s limited economic capacity and restricted access to foreign exchange make hard currency an important resource for supporting international transactions and external economic needs. These constraints have become more significant following the implementation of international sanctions that restrict North Korea’s access to trade. Using a qualitative descriptive method through literature review and document analysis, this study examines reports from the United Nations Panel of Experts, Chainalysis, FATF, FinCEN, MSMT, and other relevant sources. Hans J. Morgenthau’s Classical Realism Theory is employed to explain state behavior based on national interest. The findings indicate that cryptocurrency is utilized through digital asset activities, cyber capabilities, cross-border transactions, and mechanisms that enable the transfer or conversion of value into more liquid forms. These findings suggest that cryptocurrency has emerged as one of the instruments associated with North Korea’s efforts to access hard currency when access to formal economic channels becomes increasingly limited
Approved by Teddy
Keywords: North Korea; Cryptocurrency